A Wet Chemical Synthesis and Characterization of Mwcnt-Starch Biocomposites (Journal of Bangladesh Academy of Sciences, 2020)
MWCNT/starch composites were prepared by simple solution casting method by incorporating upto 1.0 wt. % of multi-walled carbon nanotubes (MWCNTs) as reinforcing fillers in the starch matrix. Gelatin was used as dispersing agent to disperse the MWCNTs into aqueous solution and glycerol was used as plasticizer to form composites. SEM images of the MWCNT/starch composite show the homogenous surface of the composite where CNTs are embedded into the starch matrices. XRD spectra of the composite show no characteristic peaks of CNTs in the starch matrix. FTIR spectra show peaks at around 3435 and 2927 cm-1 indicating that the covalent bonds between –OH groups and C-H groups of soluble starch and CNT were formed in the composite. Electrical conductivity of the composite was enhanced from 2.85×10-9to 5.28× 10-8 S/m due to the addition of CNTs at room temperature and decreased with the increase of temperature. UV visible spectra showed increasing absorption with increasing CNTs content in the composite. TGA analysis demonstrated the stability of the MWCNT/starch composite.Journal of Bangladesh Academy of Sciences, Vol. 44, No. 1, 43-52, 2020